Taking Stock of Recent Migration Flows in the European Union - World Bank (World Bank, 2012)
Expanded employment opportunities across the continent have been one of the most significant changes to have taken place in Europe during the past 50 years. Since the inception of the European Economic Community in 1957 involving 6 countries (Belgium, France, Italy, Luxembourg, the Netherlands and West Germany) with a combined population of less than 200 million, the European Union (EU) has grown to encompass nearly 500 million people across 27 member countries that produce, in total, about 30 percent of the world's total gross domestic product. May 2010 marked the six-year anniversary of the inclusion of eight countries from Central and Eastern Europe (Czech Republic, Estonia, Hungary, Latvia, Lithuania, Poland, the Slovak Republic and Slovenia) into the EU, followed by Romania and Bulgaria in January 2007. An important consequence of these 10 new member states (henceforth EU10) joining the EU has been to expand the internal EU labor market, albeit to varying extents for nationals of different member countries. Migration flows out of the EU10 following the 2004 enlargement is hampered by various technical and data constraints. As a result, the policy debates on the welfare consequences of migration following enlargement for both the host and sender countries have often been based on speculation and ideology rather than on the empirical evidence per se. Following the accession of EU10 countries to the EU, how large were the ensuing flows of migrant workers, and what were their main socio-economic characteristics?-in particular, how do migrants from within the EU compare to those from countries outside the EU? Are migrants poorer than the native-born population?-do they impose a high economic and social burden on the countries where they currently reside? Addressing these and other such key issues of policy interest are among the main questions addressed by this report. Using information from a variety of data sources, it takes stock of the nature, extent, and impact of EU migration following EU10 accession, and synthesizes the main lessons from this experience for future migration policy. In particular, the report highlights the positive contributions made by migrants in their host countries, as well as documents the growing importance of remittances in receiving countries.